Teaching repair versus replacement of direct composite resin restorations: A cross-sectional study across dental schools in Malaysia - Umer Daood; Preena Sidhu; Omer Sheriff Sultan; Normaliza Ab Malik; Liang Lin Seow; Nairn H F Wilson; Christopher D. Lynch; Sahar Fatima; Igor R. Blum (Elsevier BV, 2026)
Indexed by WOS / SCOPUS / ERA